The challenges of teaching in elementary education in times of social isolation (Research, Society and Development, 2021)
The teaching and learning process has, over the years, demonstrated the need for reformulation, as technological developments allow students quick access to a large volume of information. With the scenario created by the Covid-19 pandemic, education will no longer be the same and, in the midst of the uncertainties and the new directions that everyone was forced to trace, society continues in search of effective solutions for the most diverse segments. The period of social isolation brought, among other issues, the need to reinvent, advance and consolidate technology. With remote classes, discussions were opened and, with them, there was room for adaptations by teachers, students, parents and others involved in the teaching process. Hence the need to assess the students' level of learning and the quality of teaching in this emergency situation. The use of methodologies that allow measuring and assisting in the educational development of students, in order to present resources to teachers to meet the needs observed.